게이미피케이션 앱의 의사소통 효과: 앱 <모두의 이웃>을 중심으로 - 강승헌; 정지용; 박성진; 김상균 (디지털콘텐츠학회논문지, 19(7), 2018)
4차 산업혁명 시대를 살아가는 인재의 핵심역량 중 하나로 의사소통 능력이 강조되고 있다. 하지만 개인 학습 위주의 전통적 교육 시스템에서는 충분한 의사소통의 기회를 제공하지 못하고 있다는 의견이 지배적이다. 본 논문은 모바일 앱을 활용하여 의사소통을 활성화하는 방법을 제안한다. 본 연구에서는 <모두의 이웃> 모바일 앱을 개발하여, 대학생들이 이틀 동안 이 앱을 활용하게 한 후에 설문조사를 통해 의사소통 관련 효과를 분석하였다. 결과를 보면 재미와 의사소통에 대하여 모두 효과가 있었다. 실험 결과를 바탕으로 본 논문에서 제안한 앱이 사람들 간의 소통 활성화, 관심 증대 및 협력적 사고력 향상에 기여할 것으로 기대한다. Communication skills are emphasized as one of the key competencies of the people who are living in the fourth industrial revolution era. However, it is widely believed that traditional education systems focused on individual learning do not provide sufficient communication opportunities. This paper proposes a method to activate communication using mobile app. In this study, <Everybody’s Neighbor> app was developed and used by college students for two days, and then analyzed the communication-related effects through questionnaires. The results showed that both fun and communication were effective. Based on the experimental results, it is expected that the proposed app in this paper will contribute to activation of communication among people, increase of interest among members, and improvement of cooperative thinking ability. KCI Citation Count: 4